We've updated our
Privacy Policy effective December 15. Please read our updated Privacy Policy and tap

Study Guides > College Algebra

Exponential and Logarithmic Equations

In 1859, an Australian landowner named Thomas Austin released 24 rabbits into the wild for hunting. Because Australia had few predators and ample food, the rabbit population exploded. In fewer than ten years, the rabbit population numbered in the millions. Uncontrolled population growth, as in the wild rabbits in Australia, can be modeled with exponential functions. Equations resulting from those exponential functions can be solved to analyze and make predictions about exponential growth. In this section, we will learn techniques for solving exponential functions.

Exponential Equations

The first technique we will introduce for solving exponential equations involves two functions with like bases. Recall that the one-to-one property of exponential functions tells us that, for any real numbers b, S, and T, where b>0, b1b>0,\text{ }b\ne 1, bS=bT{b}^{S}={b}^{T} if and only if = T. In other words, when an exponential equation has the same base on each side, the exponents must be equal. This also applies when the exponents are algebraic expressions. Therefore, we can solve many exponential equations by using the rules of exponents to rewrite each side as a power with the same base. Then, we use the fact that exponential functions are one-to-one to set the exponents equal to one another, and solve for the unknown. For example, consider the equation 34x7=32x3{3}^{4x - 7}=\frac{{3}^{2x}}{3}. To solve for x, we use the division property of exponents to rewrite the right side so that both sides have the common base, 3. Then we apply the one-to-one property of exponents by setting the exponents equal to one another and solving for x:

34x7=32x334x7=32x31Rewrite 3 as 31.34x7=32x1Use the division property of exponents.4x7=2x1 Apply the one-to-one property of exponents.2x=6Subtract 2x and add 7 to both sides.x=3Divide by 3.\begin{array}{l}{3}^{4x - 7}\hfill & =\frac{{3}^{2x}}{3}\hfill & \hfill \\ {3}^{4x - 7}\hfill & =\frac{{3}^{2x}}{{3}^{1}}\hfill & {\text{Rewrite 3 as 3}}^{1}.\hfill \\ {3}^{4x - 7}\hfill & ={3}^{2x - 1}\hfill & \text{Use the division property of exponents}\text{.}\hfill \\ 4x - 7\hfill & =2x - 1\text{ }\hfill & \text{Apply the one-to-one property of exponents}\text{.}\hfill \\ 2x\hfill & =6\hfill & \text{Subtract 2}x\text{ and add 7 to both sides}\text{.}\hfill \\ x\hfill & =3\hfill & \text{Divide by 3}\text{.}\hfill \end{array}

A General Note: Using the One-to-One Property of Exponential Functions to Solve Exponential Equations

For any algebraic expressions S and T, and any positive real number b1b\ne 1, bS=bT if and only if S=T{b}^{S}={b}^{T}\text{ if and only if }S=T

How To: Given an exponential equation with the form bS=bT{b}^{S}={b}^{T}, where S and T are algebraic expressions with an unknown, solve for the unknown.

  1. Use the rules of exponents to simplify, if necessary, so that the resulting equation has the form bS=bT{b}^{S}={b}^{T}.
  2. Use the one-to-one property to set the exponents equal.
  3. Solve the resulting equation, = T, for the unknown.

Example: Solving an Exponential Equation with a Common Base

Solve 2x1=22x4{2}^{x - 1}={2}^{2x - 4}.

Answer: 2x1=22x4The common base is 2. x1=2x4By the one-to-one property the exponents must be equal. x=3Solve for x.\begin{array}{l} {2}^{x - 1}={2}^{2x - 4}\hfill & \text{The common base is }2.\hfill \\ \text{ }x - 1=2x - 4\hfill & \text{By the one-to-one property the exponents must be equal}.\hfill \\ \text{ }x=3\hfill & \text{Solve for }x.\hfill \end{array}

Try It

Solve 52x=53x+2{5}^{2x}={5}^{3x+2}.

Answer: x=2x=–2

Example: Solving Equations by Rewriting Roots with Fractional Exponents to Have a Common Base

Solve 25x=2{2}^{5x}=\sqrt{2}.

Answer: 25x=212Write the square root of 2 as a power of 2.5x=12Use the one-to-one property.x=110Solve for x.\begin{array}{l}{2}^{5x}={2}^{\frac{1}{2}}\hfill & \text{Write the square root of 2 as a power of }2.\hfill \\ 5x=\frac{1}{2}\hfill & \text{Use the one-to-one property}.\hfill \\ x=\frac{1}{10}\hfill & \text{Solve for }x.\hfill \end{array}

Try It

Solve 5x=5{5}^{x}=\sqrt{5}.

Answer: x=12x=\frac{1}{2}

Use logarithms to solve exponential equations

Sometimes the terms of an exponential equation cannot be rewritten with a common base. In these cases, we solve by taking the logarithm of each side. Recall, since log(a)=log(b)\mathrm{log}\left(a\right)=\mathrm{log}\left(b\right) is equivalent to = b, we may apply logarithms with the same base on both sides of an exponential equation.

How To: Given an exponential equation in which a common base cannot be found, solve for the unknown.

  1. Apply the logarithm of both sides of the equation.
    • If one of the terms in the equation has base 10, use the common logarithm.
    • If none of the terms in the equation has base 10, use the natural logarithm.
  2. Use the rules of logarithms to solve for the unknown.

Example: Solving an Equation Containing Powers of Different Bases

Solve 5x+2=4x{5}^{x+2}={4}^{x}.

Answer:  5x+2=4xThere is no easy way to get the powers to have the same base. ln5x+2=ln4xTake ln of both sides. (x+2)ln5=xln4Use laws of logs. xln5+2ln5=xln4Use the distributive law. xln5xln4=2ln5Get terms containing x on one side, terms without x on the other.x(ln5ln4)=2ln5On the left hand side, factor out an x. xln(54)=ln(125)Use the laws of logs. x=ln(125)ln(54)Divide by the coefficient of x.\begin{array}{l}\text{ }{5}^{x+2}={4}^{x}\hfill & \text{There is no easy way to get the powers to have the same base}.\hfill \\ \text{ }\mathrm{ln}{5}^{x+2}=\mathrm{ln}{4}^{x}\hfill & \text{Take ln of both sides}.\hfill \\ \text{ }\left(x+2\right)\mathrm{ln}5=x\mathrm{ln}4\hfill & \text{Use laws of logs}.\hfill \\ \text{ }x\mathrm{ln}5+2\mathrm{ln}5=x\mathrm{ln}4\hfill & \text{Use the distributive law}.\hfill \\ \text{ }x\mathrm{ln}5-x\mathrm{ln}4=-2\mathrm{ln}5\hfill & \text{Get terms containing }x\text{ on one side, terms without }x\text{ on the other}.\hfill \\ x\left(\mathrm{ln}5-\mathrm{ln}4\right)=-2\mathrm{ln}5\hfill & \text{On the left hand side, factor out an }x.\hfill \\ \text{ }x\mathrm{ln}\left(\frac{5}{4}\right)=\mathrm{ln}\left(\frac{1}{25}\right)\hfill & \text{Use the laws of logs}.\hfill \\ \text{ }x=\frac{\mathrm{ln}\left(\frac{1}{25}\right)}{\mathrm{ln}\left(\frac{5}{4}\right)}\hfill & \text{Divide by the coefficient of }x.\hfill \end{array}

Try It

Solve 2x=3x+1{2}^{x}={3}^{x+1}.

Answer: x=ln3ln(23)x=\frac{\mathrm{ln}3}{\mathrm{ln}}\left(23\right)

Q & A

Does every equation of the form y=Aekty=A{e}^{kt} have a solution?

No. There is a solution when k0k\ne 0, and when y and A are either both 0 or neither 0, and they have the same sign. An example of an equation with this form that has no solution is 2=3et2=-3{e}^{t}.

Example: Solving an Equation That Can Be Simplified to the Form y=Aekty=A{e}^{kt}

Solve 4e2x+5=124{e}^{2x}+5=12.

Answer: 4e2x+5=124e2x=7Combine like terms.e2x=74Divide by the coefficient of the power.2x=ln(74)Take ln of both sides.x=12ln(74)Solve for x.\begin{array}{l}4{e}^{2x}+5=12\hfill & \hfill \\ 4{e}^{2x}=7\hfill & \text{Combine like terms}.\hfill \\ {e}^{2x}=\frac{7}{4}\hfill & \text{Divide by the coefficient of the power}.\hfill \\ 2x=\mathrm{ln}\left(\frac{7}{4}\right)\hfill & \text{Take ln of both sides}.\hfill \\ x=\frac{1}{2}\mathrm{ln}\left(\frac{7}{4}\right)\hfill & \text{Solve for }x.\hfill \end{array}

Try It

Solve 3+e2t=7e2t3+{e}^{2t}=7{e}^{2t}.

Answer: t=ln(12)=12ln(2)t=\mathrm{ln}\left(\frac{1}{\sqrt{2}}\right)=-\frac{1}{2}\mathrm{ln}\left(2\right)

Q & A

Does every logarithmic equation have a solution?

No. Keep in mind that we can only apply the logarithm to a positive number. Always check for extraneous solutions.

Logarithmic Equations

We have already seen that every logarithmic equation logb(x)=y{\mathrm{log}}_{b}\left(x\right)=y is equivalent to the exponential equation by=x{b}^{y}=x. We can use this fact, along with the rules of logarithms, to solve logarithmic equations where the argument is an algebraic expression. For example, consider the equation log2(2)+log2(3x5)=3{\mathrm{log}}_{2}\left(2\right)+{\mathrm{log}}_{2}\left(3x - 5\right)=3. To solve this equation, we can use rules of logarithms to rewrite the left side in compact form and then apply the definition of logs to solve for x:

log2(2)+log2(3x5)=3 log2(2(3x5))=3Apply the product rule of logarithms. log2(6x10)=3Distribute. 23=6x10Apply the definition of a logarithm. 8=6x10Calculate 23. 18=6xAdd 10 to both sides. x=3Divide by 6.\begin{array}{l}{\mathrm{log}}_{2}\left(2\right)+{\mathrm{log}}_{2}\left(3x - 5\right)=3\hfill & \hfill \\ \text{ }{\mathrm{log}}_{2}\left(2\left(3x - 5\right)\right)=3\hfill & \text{Apply the product rule of logarithms}.\hfill \\ \text{ }{\mathrm{log}}_{2}\left(6x - 10\right)=3\hfill & \text{Distribute}.\hfill \\ \text{ }{2}^{3}=6x - 10\hfill & \text{Apply the definition of a logarithm}.\hfill \\ \text{ }8=6x - 10\hfill & \text{Calculate }{2}^{3}.\hfill \\ \text{ }18=6x\hfill & \text{Add 10 to both sides}.\hfill \\ \text{ }x=3\hfill & \text{Divide by 6}.\hfill \end{array}

A General Note: Using the Definition of a Logarithm to Solve Logarithmic Equations

For any algebraic expression S and real numbers b and c, where b>0, b1b>0,\text{ }b\ne 1,

logb(S)=cif and only ifbc=S{\mathrm{log}}_{b}\left(S\right)=c\text{if and only if}{b}^{c}=S

Example: Using Algebra to Solve a Logarithmic Equation

Solve 2lnx+3=72\mathrm{ln}x+3=7.

Answer: 2lnx+3=7 2lnx=4Subtract 3. lnx=2Divide by 2. x=e2Rewrite in exponential form.\begin{array}{l}2\mathrm{ln}x+3=7\hfill & \hfill \\ \text{ }2\mathrm{ln}x=4\hfill & \text{Subtract 3}.\hfill \\ \text{ }\mathrm{ln}x=2\hfill & \text{Divide by 2}.\hfill \\ \text{ }x={e}^{2}\hfill & \text{Rewrite in exponential form}.\hfill \end{array}

Try It

Solve 6+lnx=106+\mathrm{ln}x=10.

Answer: x=e4x={e}^{4}

Example: Using a Graph to Understand the Solution to a Logarithmic Equation

Solve lnx=3\mathrm{ln}x=3.

Answer: lnx=3x=e3Use the definition of the natural logarithm.\begin{array}{l}\mathrm{ln}x=3\hfill & \hfill \\ x={e}^{3}\hfill & \text{Use the definition of the natural logarithm}\text{.}\hfill \end{array} Below is a graph of the equation. On the graph, the x-coordinate of the point at which the two graphs intersect is close to 20. In other words e320{e}^{3}\approx 20. A calculator gives a better approximation: e320.0855{e}^{3}\approx 20.0855.

Graph of two questions, y=3 and y=ln(x), which intersect at the point (e^3, 3) which is approximately (20.0855, 3). The graphs of y=lnxy=\mathrm{ln}x and y = 3 cross at the point (e3,3)\left(e^3,3\right), which is approximately (20.0855, 3).

Try It

Use a graphing calculator to estimate the approximate solution to the logarithmic equation 2x=1000{2}^{x}=1000 to 2 decimal places.

Answer: x9.97x\approx 9.97

Use the one-to-one property of logarithms to solve logarithmic equations

As with exponential equations, we can use the one-to-one property to solve logarithmic equations. The one-to-one property of logarithmic functions tells us that, for any real numbers > 0, > 0, > 0 and any positive real number b, where b1b\ne 1,

logbS=logbT if and only if S=T{\mathrm{log}}_{b}S={\mathrm{log}}_{b}T\text{ if and only if }S=T.

For example,

If log2(x1)=log2(8),then x1=8\text{If }{\mathrm{log}}_{2}\left(x - 1\right)={\mathrm{log}}_{2}\left(8\right),\text{then }x - 1=8.

So, if x1=8x - 1=8, then we can solve for x, and we get = 9. To check, we can substitute = 9 into the original equation: log2(91)=log2(8)=3{\mathrm{log}}_{2}\left(9 - 1\right)={\mathrm{log}}_{2}\left(8\right)=3. In other words, when a logarithmic equation has the same base on each side, the arguments must be equal. This also applies when the arguments are algebraic expressions. Therefore, when given an equation with logs of the same base on each side, we can use rules of logarithms to rewrite each side as a single logarithm. Then we use the fact that logarithmic functions are one-to-one to set the arguments equal to one another and solve for the unknown. For example, consider the equation log(3x2)log(2)=log(x+4)\mathrm{log}\left(3x - 2\right)-\mathrm{log}\left(2\right)=\mathrm{log}\left(x+4\right). To solve this equation, we can use the rules of logarithms to rewrite the left side as a single logarithm, and then apply the one-to-one property to solve for x:

log(3x2)log(2)=log(x+4) log(3x22)=log(x+4)Apply the quotient rule of logarithms. 3x22=x+4Apply the one to one property of a logarithm. 3x2=2x+8Multiply both sides of the equation by 2. x=10Subtract 2x and add 2.\begin{array}{l}\mathrm{log}\left(3x - 2\right)-\mathrm{log}\left(2\right)=\mathrm{log}\left(x+4\right)\hfill & \hfill \\ \text{ }\mathrm{log}\left(\frac{3x - 2}{2}\right)=\mathrm{log}\left(x+4\right)\hfill & \text{Apply the quotient rule of logarithms}.\hfill \\ \text{ }\frac{3x - 2}{2}=x+4\hfill & \text{Apply the one to one property of a logarithm}.\hfill \\ \text{ }3x - 2=2x+8\hfill & \text{Multiply both sides of the equation by }2.\hfill \\ \text{ }x=10\hfill & \text{Subtract 2}x\text{ and add 2}.\hfill \end{array}

To check the result, substitute = 10 into log(3x2)log(2)=log(x+4)\mathrm{log}\left(3x - 2\right)-\mathrm{log}\left(2\right)=\mathrm{log}\left(x+4\right).

log(3(10)2)log(2)=log((10)+4) log(28)log(2)=log(14) log(282)=log(14)The solution checks.\begin{array}{l}\mathrm{log}\left(3\left(10\right)-2\right)-\mathrm{log}\left(2\right)=\mathrm{log}\left(\left(10\right)+4\right)\hfill & \hfill \\ \text{ }\mathrm{log}\left(28\right)-\mathrm{log}\left(2\right)=\mathrm{log}\left(14\right)\hfill & \hfill \\ \text{ }\mathrm{log}\left(\frac{28}{2}\right)=\mathrm{log}\left(14\right)\hfill & \text{The solution checks}.\hfill \end{array}

A General Note: Using the One-to-One Property of Logarithms to Solve Logarithmic Equations

For any algebraic expressions S and T and any positive real number b, where b1b\ne 1,

logbS=logbT if and only if S=T{\mathrm{log}}_{b}S={\mathrm{log}}_{b}T\text{ if and only if }S=T

Note, when solving an equation involving logarithms, always check to see if the answer is correct or if it is an extraneous solution.

How To: Given an equation containing logarithms, solve it using the one-to-one property.

  1. Use the rules of logarithms to combine like terms, if necessary, so that the resulting equation has the form logbS=logbT{\mathrm{log}}_{b}S={\mathrm{log}}_{b}T.
  2. Use the one-to-one property to set the arguments equal.
  3. Solve the resulting equation, ST, for the unknown.

Example: Solving an Equation Using the One-to-One Property of Logarithms

Solve ln(x2)=ln(2x+3)\mathrm{ln}\left({x}^{2}\right)=\mathrm{ln}\left(2x+3\right).

Answer:  ln(x2)=ln(2x+3) x2=2x+3Use the one-to-one property of the logarithm. x22x3=0Get zero on one side before factoring.(x3)(x+1)=0Factor using FOIL. x3=0 or x+1=0If a product is zero, one of the factors must be zero. x=3 or x=1Solve for x.\begin{array}{l}\text{ }\mathrm{ln}\left({x}^{2}\right)=\mathrm{ln}\left(2x+3\right)\hfill & \hfill \\ \text{ }{x}^{2}=2x+3\hfill & \text{Use the one-to-one property of the logarithm}.\hfill \\ \text{ }{x}^{2}-2x - 3=0\hfill & \text{Get zero on one side before factoring}.\hfill \\ \left(x - 3\right)\left(x+1\right)=0\hfill & \text{Factor using FOIL}.\hfill \\ \text{ }x - 3=0\text{ or }x+1=0\hfill & \text{If a product is zero, one of the factors must be zero}.\hfill \\ \text{ }x=3\text{ or }x=-1\hfill & \text{Solve for }x.\hfill \end{array}

Analysis of the Solution

There are two solutions: = 3 or = –1. The solution = –1 is negative, but it checks when substituted into the original equation because the argument of the logarithm functions is still positive.

Try It

Solve ln(x2)=ln1\mathrm{ln}\left({x}^{2}\right)=\mathrm{ln}1.

Answer: x=1x=1 or x=1x=–1

Key Equations

One-to-one property for exponential functions For any algebraic expressions S and T and any positive real number b, wherebS=bT{b}^{S}={b}^{T} if and only if S = T.
Definition of a logarithm For any algebraic expression S and positive real numbers b and c, where b1b\ne 1,logb(S)=c{\mathrm{log}}_{b}\left(S\right)=c if and only if bc=S{b}^{c}=S.
One-to-one property for logarithmic functions For any algebraic expressions S and T and any positive real number b, where b1b\ne 1, logbS=logbT{\mathrm{log}}_{b}S={\mathrm{log}}_{b}T if and only if ST.

Key Concepts

  • We can solve many exponential equations by using the rules of exponents to rewrite each side as a power with the same base. Then we use the fact that exponential functions are one-to-one to set the exponents equal to one another and solve for the unknown.
  • When we are given an exponential equation where the bases are explicitly shown as being equal, set the exponents equal to one another and solve for the unknown.
  • When we are given an exponential equation where the bases are not explicitly shown as being equal, rewrite each side of the equation as powers of the same base, then set the exponents equal to one another and solve for the unknown.
  • When an exponential equation cannot be rewritten with a common base, solve by taking the logarithm of each side.
  • We can solve exponential equations with base e, by applying the natural logarithm of both sides because exponential and logarithmic functions are inverses of each other.
  • After solving an exponential equation, check each solution in the original equation to find and eliminate any extraneous solutions.
  • When given an equation of the form logb(S)=c{\mathrm{log}}_{b}\left(S\right)=c, where S is an algebraic expression, we can use the definition of a logarithm to rewrite the equation as the equivalent exponential equation bc=S{b}^{c}=S, and solve for the unknown.
  • We can also use graphing to solve equations with the form logb(S)=c{\mathrm{log}}_{b}\left(S\right)=c. We graph both equations y=logb(S)y={\mathrm{log}}_{b}\left(S\right) and = c on the same coordinate plane and identify the solution as the x-value of the intersecting point.
  • When given an equation of the form logbS=logbT{\mathrm{log}}_{b}S={\mathrm{log}}_{b}T, where S and T are algebraic expressions, we can use the one-to-one property of logarithms to solve the equation = T for the unknown.
  • Combining the skills learned in this and previous sections, we can solve equations that model real world situations, whether the unknown is in an exponent or in the argument of a logarithm.

Glossary

extraneous solution a solution introduced while solving an equation that does not satisfy the conditions of the original equation

Licenses & Attributions